Prevalence of Blastocystis in Geese Reproductive Flocks - Piotr Falkowski; Andrzej Gaweł; Kamila Bobrek (Animals, 2022)
Blastocystis is a unicellular, anaerobic protozoan that has a low specificity for the hosts, and it could be a zoonosis. There are not many data about the occurrence of Blastocystis in bird species, and this study aimed to check the prevalence of Blastocystis infection in reproductive geese flocks. The result obtained showed that a parasite was present in 46.5% of tested flocks. The extensiveness of the Blastocystis invasion in reproductive geese flocks was low because the genetic material of parasites was found only in 7.48% of samples. There was no correlation between the infection and the bird’s age or the flock size. The data obtained showed that geese could be the source of infections in humans who have contact with carriers of the infection.